“Análisis de la sostenibilidad y competitividad de las empresas turísticas de hospedaje del Cantón Sigchos, provincia de Cotopaxi” - Yanez Ibujes, Anthony Giovanny (2023)
This research is focused on the analysis of factors related to sustainability and companies in the hosting category at Sigchos town. In fact, to meet this objective, two methodologies are used; InnovaRSE Navarra (2020), for the sustainability analysis, and the IDB (Inter – American Developed Bank) by Saavedra García (2012) methodology for the sustainability analysis. The participants in the interviews were 7 managers or owners corresponding to the companies in the study area described above. Through the quantitative modality, transversa type, it was possible to demonstrate through statistical graphs the results obtained that the 7 lodging companies are in the category of good sustainable practices, excelling in the social and environment dimensions, demonstrating that tourist activity benefits local suppliers, human talent, and good environment practices, with an average of (6.5) equivalent to (7). According to the individual results, 6 companies are located in the category of improvement processes with averages of: (4 – 5 – and 6), these also present, showing deficiencies in: balance control processes, support of market – focused sales, and tax records. The Llullu Llama hostel stands out from the other accommodations with an average of (9.93), being placed in the category of good sustainable practices, demonstrates the result by managerial and administrative control that influence the following two dimensions. On the other hand, in the competitiveness variable, the 7 companies are in a range of (o% to 20%), with a percentage of (12.87%), in a category of very low competitiveness, these show problems such as: planning, control, and administrative processes that affect the areas and sub – areas of marketing, accounting, production, and information systems.